Weltweit und virtuell - Praxisbeispiele aus dem digitalen Hochschulmarketing - GATE, Germany (Schriftenreihe Hochschulmarketing, 2016)
"The study presents examples of good practice in the use of digital tools for international university marketing. This includes websites, apps, social media, webinars, virtual fairs, digital learning and teaching formats and a customer relationship management system. The presented projects from Germany and other countries in Europe offer innovative models and recommended actions that universities can adapt for their own international marketing."